Intestinal Infarction and Portal Vein Thrombosis in a Patient with Henoch Schonlein Purpura. (14th October 2012) - Abebe, Mekdess; Patnaik, Asha; Miller, Frederick; Roppelt, Heidi; Wadhwa, Nand K.; Abate, Mersema; Nord, Edward P.
Abstract : Henoch Schonlein purpura is a systemic vasculitis that commonly affects children and teenagers but also affects adults of all ages. In most instances it has a benign course. Organ involvement, particularly in adults, and notably the kidneys and gastrointestinal tract may require therapeutic intervention and may have a less favorable outcome. We report a case of a 58-year-old man who presented with purpura and who rapidly developed catastrophic intestinal vasculitis, leading to his demise.